Microglial progranulin differently regulates hypothalamic lysosomal function in lean and obese conditions via cleavage-dependent mechanisms - Chae Beom Park; Chan Hee Lee; Gil Myoung Kang; Se Hee Min; Min-Seon Kim (Journal of Neuroinflammation)
Abstract Progranulin (PGRN) is a secretory precursor protein composed of 7.5 granulins (GRNs). Mutations in the PGRN-encoding gene Grn have been associated with neurodegenerative diseases. In our previous study, we found that Grn depletion in microglia disrupted glucose metabolism in mice fed a normal chow diet (NCD) but prevented the development of obesity in mice on a high-fat diet (HFD). Given that PGRN regulates lysosomal functions, we investigated lysosomal changes in the hypothalamus of mice with microglia-specific Grn depletion. Here we report that microglia-specific Grn depletion affects the lysosomes of hypothalamic proopiomelanocortin (POMC) neurons and microglia in diet-dependent fashion. Under NCD conditions, microglial Grn depletion led to increased lysosome mass, reduced lysosomal degradative capacity, and accumulation of lipofuscin and cytoplasmic TDP-43 in hypothalamic cells, indicative of lysosomal stress and dysfunction. In contrast, under HFD conditions, the absence of microglial Grn suppressed HFD-induced hypothalamic lysosomal stress. In cultured hypothalamic neurons and microglia, PGRN treatment enhanced lysosomal function, an effect inhibited by PGRN cleavage but restored when its cleavage was blocked. Since HFD feeding promotes the cleavage of hypothalamic PGRN into multi-GRNs and GRNs, the diet-dependent lysosomal changes observed in microglial Grn-depleted mice may be linked to PGRN cleavage. We also demonstrated that intracerebroventricular injection of bafilomycin, which induces lysosomal stress, resulted in microglial activation, inflammation, disrupted POMC neuronal circuitry, and impaired leptin signaling in the hypothalamus—common features of obesity. Our results indicate that microglial PGRN plays an important role in maintaining hypothalamic lysosomal function under healthy diet conditions, whereas increased cleavage of microglial PGRN in states of overnutrition disrupts hypothalamic lysosomal function, thereby fostering hypothalamic inflammation and obesity.